Effect of lipid infusion on bile composition and lithogenicity in patients without cholesterol gall stones. Issue 10 (October 1992) - Rubin, M; Halpern, Z; Charach, G; Dvir, A; Antebi, E; Gilat, T; Lichtenberg, D
Abstract : A prospective study was performed to investigate the effect of short term lipid infusion on bile composition and its lithogenicity in humans. Thirty five patients shown to be free of cholesterol gall stones participated in the study. Starting 48 hours before surgery they were infused randomly with a lipid emulsion of either long chain triglycerides (LCT) or a mixture of medium and long chain triglycerides (MCT/LCT) (50%/50%) for six hours each 24 hours. A group of patients infused with a solution of 5% glucose in NaCl 0.9% served as a control. Bile samples were obtained by puncture of the gall bladder during operation. Both lipids caused an increase in biliary cholesterol and phospholipids but this effect was more pronounced and significant (p < 0.001) only with the MCT/LCT emulsion. The fatty acid composition of biliary phospholipids was not affected by either lipid infusion. The cholesterol saturation index increased significantly (p < 0.005) with the MCT/LCT emulsion and there was shortening in the nucleation time but this was not significant. There was no effect on the distribution of cholesterol between micelles and vesicles. This study shows that infusion of MCT/LCT lipid emulsion can cause lithogenic changes in bile composition in humans and may thus contribute to sludge formation and cholelithiasis during long term parenteral nutrition.